Advice from the Scientific Advisory Board of the Organisation for the Prohibition of Chemical Weapons on riot control agents in connection to the Chemical Weapons Convention. Issue 73 (19th December 2018) - Timperley, Christopher M.; Forman, Jonathan E.; Åas, Pal; Abdollahi, Mohammad; Benachour, Djafer; Al-Amri, Abdullah Saeed; Baulig, Augustin; Becker-Arnold, Renate; Borrett, Veronica; Cariño, Flerida A.; Curty, Christophe; Gonzalez, David; et al.
Abstract : Chemicals that meet the criteria of a riot control agent as defined by the Chemical Weapons Convention (an international chemical disarmament and non-proliferation treaty) are reviewed by the Scientific Advisory Board of the Organisation for the Prohibition of Chemical Weapons. Abstract : Compounds that cause powerful sensory irritation to humans were reviewed by the Scientific Advisory Board (SAB) of the Organisation for the Prohibition of Chemical Weapons (OPCW) in response to requests in 2014 and 2017 by the OPCW Director-General to advise which riot control agents (RCAs) might be subject to declaration under the Chemical Weapons Convention (the "Convention"). The chemical and toxicological properties of 60 chemicals identified from a survey by the OPCW of RCAs that had been researched or were available for purchase, and additional chemicals recognised by the SAB as having potential RCA applications, were considered. Only 17 of the 60 chemicals met the definition of a RCA under the Convention. These findings were provided to the States Parties of the Convention to inform the implementation of obligations pertaining to RCAs under this international chemical disarmament and non-proliferation treaty.